2010
DOI: 10.1007/s12663-010-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

A radiolucent lesion crossing the midline in maxilla: a rare presentation of odontogenic keratocyst in young patient

Abstract: Odontogenic Keratocyst (OKC) is a developmental non-inflammatory odontogenic cyst which is proposed to be arising from cell rests of dental lamina. Among the jaw cysts OKCs account for third most common following radicular and dentigerous cyst. Most of the studies have stated that posterior part of the mandible is the most common site, but there are inconsistencies regarding the prominent location of OKCs in the maxilla. Very few studies and cases are reported with OKCs crossing maxillary midline. If do occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…It was in 1956 that Phillipsen described OKC for epithelial developmental cysts [ 6 ]. OKCs show an occurrence of 65% to 83% in the mandible but their location in the maxillary site is conflicted [ 2 , 3 ]. OKCs that occur in regions other than the mandibular angle and especially those in the maxilla seem to be more related to systemic syndromes [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was in 1956 that Phillipsen described OKC for epithelial developmental cysts [ 6 ]. OKCs show an occurrence of 65% to 83% in the mandible but their location in the maxillary site is conflicted [ 2 , 3 ]. OKCs that occur in regions other than the mandibular angle and especially those in the maxilla seem to be more related to systemic syndromes [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Odontogenic keratocyst (OKC) is a distinctive form of developmental odontogenic cyst comprising 12% of the entire jaw cysts [ 1 ]. Considering their peculiar behaviour, varied origin, debated development, discourse treatment modalities, and high recurrence rate, OKCs have been a subject of interest for various oral surgeons and pathologists globally [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies have shown that the posterior part of the mandible is the most common site in terms of Radiographic features, but in our case we present a case of OKC in anterior region which is rare location. OKC is specified as a well-defined radiolucency that may be either unilocular or multilocular [12].…”
Section: Discussionmentioning
confidence: 99%
“…KCOT affects mandible more commonly than maxilla, with a predilection for molar-ramus area (65-83%) [5]. Till date, only a handful of cases has been reported of KCOT crossing maxillary midline [6]. When KCOT occurs in maxilla, diagnostic difficulties arise owing to lack of characteristic clinical and radiographic features [2].…”
Section: Discussionmentioning
confidence: 99%